PENGARUH RAMUAN JAMU MACAN KERAH SEBAGAI PEREDA NYERI HAID WANITA - Pingkan Angeliadara Fortuna; Aurellia Riyandita Putri; Mochammad Afif Zahir Prasetyo; Agus Refli Pangestu; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2023)
Dysmenorrhea is lower abdominal pain that sometimes extends to the waist, lower back, and thighs. For every young woman who will enter menstruation. Menstrual pain can be relieved by consuming chemical drugs or traditional medicines such as herbs. The herbal medicine in question is a macan kerah herbal medicine that is known to be efficacious for maintaining the health of the female organs, especially for relieving menstrual pain. The method used in this experiment with interviews. The results of interviews during the socialization were as much as 80% of respondents felt dystonia or menstrual pain, as many as 95% of respondents understood the socialization material regarding dystonia that had been delivered, and 85% of respondents were able to make tiger-collar herbal medicine at home. After a few days of consuming macabre herbal medicine, the researchers conducted interviews showing that as many as 90% of respondents felt the effect of tiger mackerel herb in relieving menstrual pain. Keywords: Herb Macan Kerah, Menses, Pain, dysmenorrhea